A1_2 Duck, duck... Spruce! - Dodd, Peter; Kettle, Fraser; Webb, Alex; Bayliss, Martyn; Sukaitis, Tomas (Physics Special Topics, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The H-4 Hercules was a prototype aircraft built in 1947 which was never properly flight tested. This report explores a theory that this aircraft would never have been able to fly more than a few hundred feet off of the ground due to the ground effect and that the plane was not viable for the purpose of transporting heavy military equipment. By exploring the pressure difference over the wing surfaces, the aircraft is shown to be able to reach a maximum altitude of 9,660 m and to require a minimum takeoff speed of 113.6 km/h. It is therefore shown that the aircraft would have been able to takeoff fully loaded and could have reached a high altitude successfully.Â